(untitled) (Journal of Misan Researches, 2023)
The hadeeth IkrimahMawla Ibn Abbas is not an easy matter due to the difficulty of the scientific material and how to collect it and then index it, so the starting point was with his interpretation, which was not collected according to our modest knowledge, and the research has to Interpreter” and it contains rich material that requires more than one research, it is necessary pruning it and taking a side of it, and this is what really happened. The important thing is that this is how the subject of the research is appeared, and its vocabulary must be explained, and it is known from the word “interpretation” contained in the title, and it is usual for the great commentators, they cut off the Holy Qur’an and interpret one word after another. Perhaps it will be successful, but we did the opposite, so we put titles for the verses to be discussed in order to preserve the unity of the subject. And before we know the interpretation of the man, we should know his critics on this subject, who were divided between those who praise and criticize him, and then we clarified what is related to the unification of the divine being, whether it sleeps or not, we discussed that in the topic of Sunnah and sleep, and then the stories of the prophets in a brief form. Such as Abraham, Moses, and the Prophet Muhammad. After that, there is a transmission of what was reported by Ikrimah about the People of the Book, especially the Sons of Israel, and there was a pause with the people of Hell and their clothes, as well as the same applies to the ignorant (the ignorant) and the immoral ones, after which there is something about the Shari’a rulings, which is what pertains to hunting the sea and knowing its ornaments from its prohibition, and praise be to God, Lord of the Worlds.